Grain size evolution in Cu-based shape memory alloys - Montecinos Espinoza, Susana de Los Angeles (2015)
A study of the grain growth kinetics in two shape memory alloys, CuAlBe and CuZnAl, is reported. Isothermal aging treatments at temperatures between 1023 and 1123 K were conducted, determining the grain size distribution as a function of time. The results show that the size distribution can be described by a log-normal type relationship, and is time-invariant. It was found that the arithmetic mean grain size almost coincide with the mode, which means that it is a representative parameter of the microstructure along the annealing time. The growth kinetics is strongly dependent on the aging temperature in CuZnAl, while is weakly in CuAlBe. It was verified that the grain size-time power law usually applied is not appropriate to describe the process, and an early departure from the ideal behavior is observed. The modification with a time-dependent dragging force gives a reasonable approximation to the grain growth kinetic. The obtained results are compared with the scarce data existing on this type of alloys.